2000
DOI: 10.1038/sj.gt.3301287
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus as a vector to transduce human dendritic cells for immunotherapy: abortive infection but reduced APC function

Abstract: Dendritic cells (DC) are potent antigen-presenting cells (APC). Ongoing preclinical and clinical studies exploit this capacity for the immunotherapy of tumors. We tested vaccinia virus (VV) as a vector to transduce human DC. Immature and mature DC were prepared from blood monocytes and infected with (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
80
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 67 publications
11
80
0
Order By: Relevance
“…Yet, studies on infected DC exhibited that VV was a potent inhibitor of DC maturation and severely reduced the ability of DC to induce proliferation of naïve T cells, typically one of the hallmarks of the mature DC. We and other groups also found that VV reduces the expression of CD80 and CD83 on mature DC, and, in case of CD80, also in uninfected bystander DC [30][31][32].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Yet, studies on infected DC exhibited that VV was a potent inhibitor of DC maturation and severely reduced the ability of DC to induce proliferation of naïve T cells, typically one of the hallmarks of the mature DC. We and other groups also found that VV reduces the expression of CD80 and CD83 on mature DC, and, in case of CD80, also in uninfected bystander DC [30][31][32].…”
Section: Introductionsupporting
confidence: 67%
“…Collectively, these viral interactions, which apparently function to keep the infected DC trapped to the site of VV activity, and consequently to inhibit an anti-viral immune response, lead to an intercellular communication breakdown and paralysis of professional APC. Apart from this, and in addition to recent results referring to reduced allostimulatory capacity and down-regulation of costimulatory molecules of VV-infected DC [30,31], the results of this study contribute to doubts whether WR and MVA in their current forms are suitable expression vectors for DC-based immunotherapy.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, plasmid DNA transfer into DC has not been very efficient (17), and the use of viral vectors for transduction of DC implies a more complex and laborious manipulation associated with safety issues. Moreover, DC transduced by viral vectors have been reported to have impaired function in terms of stimulatory capacity (18,19). Recently, we (20) and others (21-23) developed novel non-viral Ag loading technologies based on the passive pulsing, lipofection, and electroporation of mRNA.…”
mentioning
confidence: 99%